The Central African Republic’s Infrastructure : A Continental Perspective - Dominguez-Torres, Carolina; Foster, Vivien (2012)
Between 2000 and 2005, infrastructure contributed less than 1 percentage point to the Central African Republic's annual per capita GDP growth, despite substantial spending in the road sector. Raising the country's infrastructure endowment to that of the region's middle-income countries could boost annual growth by about 3.5 percentage points. The CAR has made significant progress in the transport, water, power, and information and communications technology (ICT) sectors. But the high cost of fuel, which raises transportation and energy costs, has been a vexing issue across all infrastructure sectors. The CAR's most pressing infrastructural challenge lies in the transport sector, which relies heavily on neighboring countries and could benefit from improved road conditions and enhanced performance at the port of Douala in Cameroon. In the power sector, the country suffers from a deteriorating infrastructure stock that it can no longer afford to maintain, and an inefficient and unreliable power supply. Additional challenges include a need for improved infrastructure in the water and sanitation and ICT sectors. Addressing the CAR's infrastructure challenges will require sustained expenditure of $346 million per year over the next decade. The nation already spends around $134 million per year on infrastructure, with $37 million a year lost to inefficiencies of various kinds. If those inefficiencies were fully eliminated, the country's annual infrastructure funding gap would be $183 million per year. Improvements in funding, coupled with the prospect of an economic rebound and prudent policies, could lift the country from its fragile state back to and beyond the prosperity standards it once enjoyed.